Carbonized MIL−100(Fe) used as support for recyclable solid acid synthesis for biodiesel production. (December 2021) - Li, Hui; Wang, Junchi; Ma, Xiaoling; Wang, Yangyang; Li, Guoning; Guo, Min; Cui, Ping; Lu, Wanpeng; Zhou, Shoujun; Yu, Mingzhi
Abstract: Solid catalyst loss is inevitable by using the traditional separation methods of centrifugation or filtration. To this end, the carbonized MIL−100(Fe) is used to support ammonium sulfate ((NH4 )2 SO4 ) for synthesizing magnetic solid acid on the purpose of biodiesel production. Influence of preparation factors of loading amount, activation temperature, and activation time on catalytic activity are initially evaluated. With that, the prepared catalyst (CIS) is comprehensively investigated to obtain the optimal esterification parameters for biodiesel production. Moreover, characterizations of TG, XRD, BET, SEM, EDS, FTIR, py−FTIR, VSM, XPS, and Hammett indicator are conducted to elucidate the structure−function relationship between physicochemical property and catalytic activity. Results indicated the CIS is a superparamagnetism material with the saturated magnetism of 22 emu/g, which could be easily recovered from mixture with external magnet. Furthermore, the maximum conversion of 95.68% is obtained with mild conditions: molar ratio of methanol/oleic acid of 8:1 and catalyst amount of 8 wt% at 70 °C for 2 h. Negligible impact is detected for CIS with presence of 5 wt% water content, even with 20 wt% water content, the conversion of 85.88% is still achieved. Graphical abstract: Image 1 Highlights: Pristine and carbonized MIL−100(Fe) are used to synthesize the magnetic solid acid. Saturated magnetism of 22 emu/g is obtained from CIS with activity of 95.68%. No impact is detected for CIS with presence of 5 wt% water content.